Antimicrobial Activity Of Pteria Penguin Against Human Pathogens From The Southeast Coast Of India - T. MOHANRAJ,; K. PRABHU,; S. LAKSHMANASENTHIL, (International Journal of Pharma and Bio Sciences, 2012)
The penguin wing oyster Pteria penguin whole body extract was obtained with different solvents. The whole body extracts were assayed for antibacterial activity using agar well diffusion technique against human pathogens. The extracts derived from acetone and chloroform exhibited broad antibacterial activity. Highest activity was exhibited against Klebsiella pneumoniae (6 mm) and Staphylococcus epidermidis (5.5 mm) by the crude extract of acetone and against Salmonella paratyphi B (5.5 mm) by the chloroform extract. The column-purified acetone fractions showed higher activity against Klebsiella pneumoniae (6 mm), Streptococcus pneumoniae (4.5 mm). The MIC of the 100% acetone fraction was found to be equally lower for the pathogens Klebsiella pneumoniae (250µg) and Staphylococcus epidermidis (250µg). Therefore 100% acetonated fraction of the extract of P. penguin can be concluded as potent antimicrobial compound against these human pathogens.